Influenciada digital: mulheres no Instagram e a convocação ao consumo de procedimentos estéticos faciais - Bulla, Rafaela Cavinato (2023)
According to the latest Census from the Brazilian Society of Plastic Surgery (SBCP), the number of purely aesthetic surgeries in Brazil grew 128% from 2009 to 2018, with 87.4% of aesthetic procedures performed worldwide in the same year being done on women (ISAPS, 2018). Combining this data with the fact that Instagram is the fastest-growing social media platform in Brazil (SOUZA, 2020), this research focuses on female reception to convocation on Instagram for the consumption of facial aesthetic procedures. The objective is to verify how the consumption of content on Instagram that promotes facial aesthetic procedures performed on women, such as facial harmonization, occurs, and whether this content functions as a convocation to consume these procedures, eventually producing desire in other female users of the network to undergo similar procedures. The theoretical discussion focuses on the construction of beauty standards related to gender issues, body control, aesthetic transformations through Instagram, and the digital influencer's insertion into the social network. Some of the cited authors include Aidar Prado, Naomi Wolf, Michel Foucault, and Issaaf Karhawi. Based on the initial observation that the call-to-action posts occur both through publications by aesthetic clinics and digital influencers, the hypothesis is that the reception is more positive when the publications come from individuals rather than brands. The methodology includes literature research, statistical data collection, exploratory research of publications from aesthetic clinics and digital influencers in the city of Joinville, Santa Catarina, and a focus group with women who follow these digital influencers.